Developmental science and psychoanalysis : integration and innovation : celebrating the renewal of the collaboration of the Yale Child Study Center and the Anna Freud Centre in Promoting Psychoanalytic Developmental Research - Mayes, Linda C., ....-; Fonagy, Peter, 1952-; Target, Mary, ....- (London : Karnac, 2007)
As a discipline, psychoanalysis began at the interface of mind and brain and has always been about those most basic questions of biology and psychology: loving, hating, what brings us together as lovers, parents and friends and what pulls us apart in conflict and hatred. These are the enduring mysteries of life and especially of early development how young children learn the language of the social world with its intertwined biological, genetic, and experiential roots and how infants translate thousands of intimate moments with their parents into a genuine, intuitive, emotional connection to other persons. Developmental neuroscience and psychology has also of late turned to these basic questions of affiliation; the challenges before us are how to facilitate open discourse and collaborations among these perspectives and practitioners that often work at very different levels of discourse. This volume is not only a first step in that process but also, through the themes of the chapters and the pairing of discussants, a beginning illustration of how the cross-disciplinary discourse might work.
Includes bibliographical references (p. 331-385) and index.
Keywords: Child Development; Child Psychology; Child psychology; Child psychotherapy; Kinderpsychologie; Kinderpsychotherapie; Psychoanalyse; Psychoanalytic Interpretation; Psychoanalytic Therapy; Psychoanalytic interpretation